From 2D to 1D functionalization: Steps towards a carbon nanotube based biomembrane sensor for curvature sensitive proteins. Issue 6 (17th February 2015) - Ostermaier, Frieder; Scharfenberg, Linda; Schneider, Kristian; Hennig, Stefan; Ostermann, Kai; Posseckardt, Juliane; Rödel, Gerhard; Mertig, Michael
<x xml:space="preserve">Abstract</x> Membrane proteins are not homogeneously distributed throughout the membrane. One proposed localization mechanism is related to membrane curvature. In this work a sensor platform has been developed that uses carbon nanotubes to create curvature in a supported lipid bilayer. The specific binding of curvature sensitive proteins to the bent areas of the membrane is investigated by fluorescence microscopy. The setup will allow to study binding kinetics of curvature sensing motifs or to use such motifs for a one‐dimensional functionalization along the CNT. Fluorescence image of EGFP labeled curvature sensitive proteins that show linear alignment on a supported lipid bilayer above dielectrophoretically deposited single‐walled carbon nanotubes.<inline-graphic xlink:href="ark:/27927/pgjwxk0q84" content-type="pssa201431723-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />